β2-adrenoceptor agonists in asthma and COPD treatment - Kołaczkowska, Małgorzata (Przewodnik Lekarza/Guide for GPs, 2006)
The basic symptom of asthma and COPD is bronchospasm, wchich is a result of chronic inflammation. In the treatment of airflow disturbances inhaled short- and long-acting β 2 -agonists are adhibited in the first place. The effect of β 2 -agonists therapeutic action is a result of β 2 -adrenergic receptors distribution. Inhaled β 2 -agonists differ in selectivity, receptor activation and the beginning and duration of activity. When combined with inhaled corticosteroids they improved lung function, and reduced symptoms and exacerbations more than an increased dose of corticosteroids. The most common side effects which occur during long-term treatment are: muscle tremor, tachycardia, hypoxemia and hypocaliemia (metabolic activity).